2014
DOI: 10.1053/j.seminoncol.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Post Hoc Analyses of Intention-to-Treat Population in Phase III Comparison of NovoTTF-100A™ System Versus Best Physician’s Choice Chemotherapy

Abstract: We performed a treatment-based analysis of data from the pivotal phase III trial of the NovoTTF-100A System™ versus best physician's choice (BPC) chemotherapy in patients with recurrent glioblastoma multiforme (GBM), with particular focus on efficacy in patients using NovoTTF Therapy as intended. Median overall survival (OS) was compared for recurrent GBM patients receiving at least one full cycle of treatment with NovoTTF-100A System or BPC chemotherapy (modified intention-to-treat [mITT] population) in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 24 publications
5
70
0
Order By: Relevance
“…The compliance with TTFields therapy in the clinical trials was tightly linked to the survival outcomes; monthly compliance above 75% was associated with higher overall survival 9,10,31 . Our cell culture experiments revealed that the surviving cells recover with a delay of 24 h after end of TTFields application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance with TTFields therapy in the clinical trials was tightly linked to the survival outcomes; monthly compliance above 75% was associated with higher overall survival 9,10,31 . Our cell culture experiments revealed that the surviving cells recover with a delay of 24 h after end of TTFields application.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical use they are applied at tumor specific frequencies via ceramic electrodes, so-called transducer arrays, adhered to the shaved scalp of the patient. The therapy compliance was tightly linked to the outcome and monthly compliance above 75% was associated with higher overall survival 9,10 . In addition, this important development in the treatment of GBM patients, the therapy may be further improved by its combination with synergistic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, median OS and PFS6 were significantly longer in these 93 patients who completed the full cycle compared with those patients receiving chemotherapy. 27,80 Interestingly, in a post-hoc analysis conducted on this randomized clinical trial, compliance in patients below 60 years of age was statistically higher compared with those above 60 (80% vs 74%, respectively; p = 0.043). 26 The importance of patient compliance cannot be overstated, as the results of the original randomized trial, 65 as well as those of a previously mentioned pilot trial, 30 demonstrated that the duration of AEF therapy was highly correlated with survival (r 2 = 0.92).…”
Section: Compliance With Aef Therapymentioning
confidence: 99%
“…For example, it has been shown that patients with favorable prognostic characteristics (such as age less than 60 years or Karnofsky Performance Scale score greater than 80%), as well as patients with tumors refractory to bevacizumab treatment, had significantly greater OS with AEF therapy in comparison with standard chemotherapy. 26,27,53 Moreover, when excluding patients who did not receive a complete cycle of treatment with AEFs, patients in the AEF cohort showed improved survival in comparison with physician's best choice chemotherapy. 80 A survival benefit was also noted when comparing AEF monotherapy to those patients receiving bevacizumab.…”
Section: Post-hoc Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation